Putting summative predicates into context - Erbach, Kurt; Alexandropoulou, Stavroula; Breheny, Richard; Mayr, Clemens; Romoli, Jacopo; Sudo, Yasutada (Proceedings of the Amsterdam Colloquium, 2024)
The present paper investigates homogeneity and non-maximality effects of summative predicates like color terms (e.g., blue). It specifically tests theoretical accounts that make diverging predictions as to whether summative predicates in positive and negative sentences exhibit non-maximality effects to the same extent. To adjudicate between these accounts, we conducted experiments that tested how the availability of non-maximal readings is modulated by the conversational context. Our results were largely symmetric: Non-maximality readings of summative predicates show similar context-sensitivity in simple positive (‘The flag is blue’) and negative sentences (‘The flag is not blue’), and under the quantifiers ‘every’ (‘Every f lag is blue’) and ‘no’ (‘No flag is blue’). We discuss the theoretical consequences of these findings in light of Romoli et al.’s (2024) observation that the non-maximal readings of plural definites are asymmetric with greater context sensitivity in the scope of ‘every’ than in the scope of ‘no’